Kleine overpeinzingen : kunst kijken in het museum. - Van Gerwen, Rob (Utrecht : Centraal Museum Utrecht, 2002)
Cézanne, Paul ; van Gogh, Vincent ; Rist, Pipilotti ; Picasso, Pablo ; Koch, Pyke ; Duchamp, Marcel ; Beuys, Joseph ; van Doesburg, Theo ; Schnabel, Julian ; Matisse, Henri ; Brancusi, Constantin ; Fontana, Lucio ; Capa, Robert
Nederlands
boek